2013
DOI: 10.1007/s12035-013-8587-3
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Hypothyroxinemia and Hypothyroidism Reduce Proliferation of Cerebellar Granule Neuron Precursors in Rat Offspring by Downregulation of the Sonic Hedgehog Signaling Pathway

Abstract: Iodine deficiency (ID)-induced hypothyroxinemia and hypothyroidism during development result in dysfunction of the central nervous system, affecting psychomotor and motor function, although the underlying mechanisms causing these alterations are still unclear. Therefore, our aim is to study the effects of developmental hypothyroxinemia, caused by mild ID, and developmental hypothyroidism, caused by severe ID or methimazole (MMZ), on the proliferation of cerebellar granule neuron precursors (CGNPs), an excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Several genes involved in cell cycle regulation and cell proliferation are found to be regulated by TH in the developing brain (Dowling et al, 2000, Bansal et al, 2005, Morte et al, 2010, Qiu et al, 2010, Wang et al, 2014). In addition, neural progenitors in the VZ of rats express TRα1, Mct8 transporters and deiodinase II, and maternal thyroid hormone deficiency leads to a delay in symmetrical divisions of these progenitors, as well as a reduced cell cycle length and a corresponding reduction of the progenitor pool (Mohan et al, 2012).…”
Section: Influence Of Ths On Brain and Cognitive Developmentmentioning
confidence: 99%
“…Several genes involved in cell cycle regulation and cell proliferation are found to be regulated by TH in the developing brain (Dowling et al, 2000, Bansal et al, 2005, Morte et al, 2010, Qiu et al, 2010, Wang et al, 2014). In addition, neural progenitors in the VZ of rats express TRα1, Mct8 transporters and deiodinase II, and maternal thyroid hormone deficiency leads to a delay in symmetrical divisions of these progenitors, as well as a reduced cell cycle length and a corresponding reduction of the progenitor pool (Mohan et al, 2012).…”
Section: Influence Of Ths On Brain and Cognitive Developmentmentioning
confidence: 99%
“…In order to clarify the underlying mechanisms of how maternal hypothyroxinemia affects the cerebellum development and function, an animal model was established by administering a mildly iodine-deficient diet to dams [102]. Subsequent results suggested a reduction in the proliferation of cerebellar granule neuron precursors in hypothyroxinemia offspring, which may be related to the downregulation of the sonic hedgehog signaling pathway.…”
Section: Cerebellummentioning
confidence: 99%
“…Other T3-regulated genes such as CNN1 (calporin), which is an actin associated protein, also exerts a control of cell cycle during neurogenesis (197). Recently, it has been found that developmental mild and severe hypothyroxinemia and MMI-induced hypothyroidism alters Shh signaling pathway in the cerebellar granule cell precursors, resulting in downregulation of D1 and D2 cyclins, of E2F1 expression, and in reduced cell proliferation (198). However, it still remains unclear to what extent thyroid hormones affect symmetrical and asymmetrical divisions of neocortical progenitor cells.…”
Section: Alterations In Cortical Development Caused By Thyroid Hormonmentioning
confidence: 99%